PERTUMBUHAN TANAMAN TERUNG UNGU (Solanum Melongena L.) PADA BERBAGAI DOSIS PUPUK ORGANIK CAIR (POC) BERBAHAN DASAR AIR CUCIAN BERAS - ADAWIYAH, ROBIATUL; MAMMA, SARAWA; ARMA, MAKMUR JAYA (Jurnal Agroteknos, 2024)
This research is motivated by the fact that eggplant production is still low because it is triggered by the condition of agricultural land which is less fertile and the limited availability of nutrients. One alternative used to overcome this is liquid organic fertilizer (LOF) from rice washing water. This research aims to determine the effect of LOF made from rice washing water on the growth of eggplant plants and to determine the treatment that has the best effect on the growth of eggplant plants. This research was carried out at the Experimental Garden Field Laboratory II and the Agrotechnology Laboratory, Agronomy Unit, Faculty of Agriculture, Halu Oloe University (HOU) Kendari, Southeast Sulawesi from August to October 2023. The design used was a randomized block design (RBD) with LOF treatment of washing water rice consisting of three levels, namely 150 mL (B1), 300 mL (B2) and 450 mL L-1 water (B3). The variables observed were stem diameter, number of leaves, leaf area, number of branches, flowering age, total dry weight and root shoot ratio (RSR). Data from observations were analyzed using variance analysis (ANOVA) and further testing using Duncan's multiple range test (DMRT) at a confidence level of 95%. The results showed that LOF treatment of rice washing water had a very significant effect on stem diameter at 56 DAP; number of leaves and total leaf area at 14, 28, 42 and 56 DAP; number of branches, and total dry weight. The best treatment to increase the growth of eggplant plants is LOF at a dose of 450 mL L-1 water.